If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 3x) + -5 = 25 (3 * 2 + 3x * 2) + -5 = 25 (6 + 6x) + -5 = 25 Reorder the terms: 6 + -5 + 6x = 25 Combine like terms: 6 + -5 = 1 1 + 6x = 25 Solving 1 + 6x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 6x = 25 + -1 Combine like terms: 1 + -1 = 0 0 + 6x = 25 + -1 6x = 25 + -1 Combine like terms: 25 + -1 = 24 6x = 24 Divide each side by '6'. x = 4 Simplifying x = 4
| 43x=53 | | 52=32-4(x-3) | | f(x)=x^35-5x^24+6x^13-8x^2+5x+3 | | x-250.5=325.5 | | 4x+16-2x=7+4x-5 | | 6x-2x-1=0 | | x+80-80=200-80 | | (5x^2)*3x=5 | | 2x-20.4=x-1.6 | | x+80=200 | | 4+16-2x=7+4x-5 | | 4x-9x+21=4x+39 | | -233=8(4v-2)+7 | | 6(4+x)=-17 | | 0=x^5+2x^3+297 | | xsquared+19x+48=0 | | 700(x)=0.9x-94 | | 16y^4+32y^2+7=0 | | 24x+25=10x+53 | | 38-(-21)= | | 700(x)=0.9-94 | | -4(4x+2)-2=-5(x+1)+2x | | t^2-2t-195=0 | | 11x-(7x-6)=14 | | 6a+5=3a+26 | | 5(z+3)=95 | | .05(x)=41475-x | | 9+3x=x+25 | | -4y-9=3y+1a | | 8x+11=-21 | | 4x+5=-6+2x+25 | | y/9=72 |